1997
DOI: 10.1073/pnas.94.6.2438
|View full text |Cite
|
Sign up to set email alerts
|

Nonsense mutation at Tyr-4046 in the DNA-dependent protein kinase catalytic subunit of severe combined immune deficiency mice

Abstract: The severe combined immune deficiency (SCID) mouse was reported as an animal model for human immune deficiency. Through the course of several studies, the DNA-dependent protein kinase catalytic subunit (DNA-PKcs) gene came to be considered a candidate for the SCIDresponsible gene. We isolated an ORF of the murine DNAPKcs gene from SCID mice and their parent strain C.B-17 mice and determined the DNA sequences. The ORF of the murine DNA-PKcs gene contained 4128-aa residues and had 78.9% homology with the human D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(114 citation statements)
references
References 38 publications
(35 reference statements)
1
112
1
Order By: Relevance
“…2G). Additionally, we demonstrated that, as with parental Prkdc scid MEFs, Prkdc scid Tn-iPSCs were also hypersensitive to ionizing radiation as expected for cells deficient in NHEJ [22][23][24] (Fig. 2H).…”
Section: Resultsmentioning
confidence: 82%
“…2G). Additionally, we demonstrated that, as with parental Prkdc scid MEFs, Prkdc scid Tn-iPSCs were also hypersensitive to ionizing radiation as expected for cells deficient in NHEJ [22][23][24] (Fig. 2H).…”
Section: Resultsmentioning
confidence: 82%
“…This was achieved by interbreeding GAA-KO mice 16 with SCID mice, 17,18 yielding GAA-KO/SCID mice. Since these mice are immune-deficient, they will not allow the assessment of adaptive (cytotoxic) immune responses to the vector.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The original GAA-KO mice were produced by targeted disruption of exon 6 of the murine GAA gene by insertion of neomyocin resistance gene (Figure 1a), the resulting homozygous 6 neo /6 neo GAAKO mice have barely detectable GAA transcripts, and no GAA protein product can be detected in their muscle tissues. 16 Immuno-deficient SCID mice have a spontaneous point mutation in the catalytic subunit of DNA-dependent protein kinase (DNA-PKc) gene (Figure 1b), resulting in the inability of T-and B-lymphocytes to mature.…”
Section: Isolation Of Gaa-ko/scid Micementioning
confidence: 99%
See 2 more Smart Citations